Correlation Between Smoking Status and Respiratory Health Among Healthcare Workers in Hospitals of Mosul City/Iraq: Korelasi Antara Status Merokok dan Kesehatan Pernapasan di Kalangan Pekerja Kesehatan Pekerja di Rumah Sakit di Kota Mosul/Irak - Hasan, Athman Abdulkareem; Hussoon, Suhair Mohammed; Muslim, Tareq Mahdi; Mohammed, Rabeea Mhaidi (Indonesian Journal on Health Science and Medicine, 2024)
This paper examines the effects of smoking on respiratory health in healthcare workers in the city of Mosul, Iraq. This was carried out in two main hospitals: Ibn Sina and Al-Salam Teaching Hospitals. A total sample of 162 participants was taken into consideration. The information obtained was through questionnaires interviews and tests of lung function, which included FVC, FEV1, and FEV1/FVC ratio. In this regard, it can be noticed that the percent distribution was: current smokers consisted of 30.9%, ex-smokers 4.3%, and nonsmokers, 64.8%. The research indicates that smoking is closely linked with asthma, bronchitis, and COVID-19. This finding reiterates the key that both smoking cessation programs targeting the smoker and improved chronic obstructive pulmonary disease control among healthcare employees are of immense importance. الْخُلَاصَةُ تَبْحَث هَذِهِ الْوَرَقَةِ فِي اثَارِ التَّدْخِين عَلَى صِحَّةِ الْجِهَازِ التَّنَفُّسِيِّ لَدَى الْعَامِلِينَ فِي مَجَالِ الرِّعَايَةِ الصِّحِّيَّةِ فِي مَدِينَةٍ الْمَوْصِل ، الْعِرَاق. تَمّ تَنْفِيذُ ذَلِكَ فِي مُسْتَشْفَىين رُئِيَسِيِّين: مُسْتَشْفَى ابْنُ سِينَا وَمُسْتَشْفَى السَّلَامُ التَّعْلِيمِيّ. تَمَّ أَخَذَ عَيْنَهُ إجْمَالِيَّة مِنْ 162 مُشَارِكًا فِي الِاعْتِبَارِ. وَكَانَتْ الْمَعْلُومَاتِ الَّتِي تَمَّ الْحُصُولِ عَلَيْهَا مِنْ خِلَالِ الِاسْتِبْيَانَات وَالْمَقَابَلَات وَاخْتِبَارَات وَظَائِفِ الرِّئَة ، وَاَلَّتِي شَمِلَتْ FVC, FEV1, وَفِي هَذَا الصَّدَدِ ، يُمْكِن مُلَاحَظَةِ أَنَّ النِّسْبَةَ الْمِئَوِيَّة لِلتَّوْزِيع كَانَتْ: الْمُدَخِّنِون الْحَالَيْون يُتَأَلَّفُونَ مِنْ 30.9 ٪ ، وَالْمَدْخُنون السَّابِقُونَ 4.3 ٪ ، وَغَيْر المُدَخِّنِين 64.8٪. تَظْهَرُ هَذِهِ الدِّرَاسَةِ أَنَّ هُنَاكَ عَلَاقَة كَبِيرَةٌ بَيْنَ حَالَةِ التَّدْخِين وَأَمْرَاض الْجِهَازِ التَّنَفُّسِيِّ مِثْل الرَّبْو وَالْتِهَاب الشُّعَبِ الْهَوَائِيَّةِ وَكَوْفيد 19. مَرَّةً أُخْرَى ، يُؤَكِّدُ هَذَا عَلَى أَنَّ بَرَامِج الْإِقْلَاعُ عَنْ التَّدْخِين الْمُسْتَهْدفه وَالتَّدْخِلات الصِّحِّيَّة التَّنَفُّسِيَّة المُحْسِنَة بَيْنَ الْعَامِلَيْنِ فِي مَجَالِ الرِّعَايَةِ الصِّحِّيَّةِ يَجِبُ أَنْ تَكُونَ مَسْأَلَةُ مُلِحَّة. Highlights: Smoking affects healthcare workers’ respiratory health in Mosul hospitals. Study links smoking to asthma, bronchitis, COVID-19, and COPD risks. Urges smoking cessation programs and improved respiratory care for healthcare staff. Keywords: Smoking, Hookah, Narghile, Lung function, FEV1, FVC, FEV1/FVC%, respiratory diseases, Healthcare workers, Hospitals